2021
DOI: 10.2147/jpr.s299680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Work Related Musculoskeletal Disorders and Associated Factors Among Bank Staff in Jimma City, Southwest Ethiopia, 2019: An Institution-Based Cross-Sectional Study

Abstract: Background: Work-related musculoskeletal disorder is one of the most important public health problems throughout the world. However, there is a paucity of knowledge on workrelated musculoskeletal disorders among bank staff in Ethiopia. Therefore, this study aimed to assess the prevalence of work-related musculoskeletal disorders and associated factors among bank staff in Jimma city, Ethiopia. Methods: Institution-based cross-sectional study was conducted from July 20 to August 20, 2019. A simple random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…In Ethiopia's workplace, health and safety practices are weak or at an infancy stage. Therefore, participants might be underdiagnosed and underreported of their work-related disorders (WRUEDs) [ 33 , 57 ], whereas in those compared countries, there might be better work-related disorders reporting and management procedures. Another possible explanation for this disparity might be due to the difference in pain perception of the workers and the level of awareness and openness to the questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia's workplace, health and safety practices are weak or at an infancy stage. Therefore, participants might be underdiagnosed and underreported of their work-related disorders (WRUEDs) [ 33 , 57 ], whereas in those compared countries, there might be better work-related disorders reporting and management procedures. Another possible explanation for this disparity might be due to the difference in pain perception of the workers and the level of awareness and openness to the questions.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived job-related stress of the participants was collected using the 8-item workplace stress scale questionnaire [ 54 ]. The instruments used in this study have been employed in previous studies conducted in the country's context [ 24 , 33 , 56 ]. The fourth part encloses characteristics of the working environment including working hours per day, the habit of taking rest breaks, type of sitting chair, working postures (sitting or standing and repetitive work), ergonomic training, and methods of carrying a laptop.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported in Addis Ababa, Mekle, Jimma, and Punjab (India). 4 , 16 , 26 , 30 A study done in Addis Ababa revealed that participants who were sitting back in a twisted position 3.5 times and sitting back bent 4 times more risk of developing WMSD than those who worked in good posture. Similar studies done in Mekele City and Jimma Town also indicated participants who worked with awkward posture 2.6 times and 4 times more likely to develop MSD than those who worked in good posture respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The scale produced a single ranking, with high scores indicated higher stress levels and vice versa. The instruments used in the current study have been employed in previous studies conducted in the country’s context 70–73…”
Section: Methodsmentioning
confidence: 99%
“…The instruments used in the current study have been employed in previous studies conducted in the country's context. [70][71][72][73] Data quality control To maintain uniformity, the questionnaire was initially created in English, translated into the local tongue of Amharic, and then translated back to English. Following appropriate training and orientation, three BSc nurses and MPH Environmental health specialist who were employed at the comprehensive specialised hospital of the University of Gondar participated in data collection.…”
Section: Variable Measurement and Definition Of Termsmentioning
confidence: 99%